Adaptation and Testing of Cognitive Behavioral Therapy Resource of Turkish Version to Reduce Dental Anxiety in Children - Aliye Tuğçe Gürcan; Elif Ayşe Tamtekin; Büşra Aydın; Gülce Esentürk; Buğra Özen; Zoe Marshman (Galenos Yayinevi, 2022)
Aim:Dental anxiety is a common problem in pediatric dentistry and reducing it with improved communication is important. This study aimed to evaluate whether anxious children give similar answers in the dental office even though they have different cultural backgrounds and to assess the international usability of the cognitive behavioral therapy tool of the Turkish version of "Your Teeth You Are In Control" intervention including "Message to the Dentist" feedback form.Materials and Methods:Two hundred and sixty-two children aged 5-15 years attending a faculty clinic and a private dental office were included in this study. The children were asked to complete the form to report how worried they felt and the levels of pain they experienced before and after their dental treatment on a scale of 1-10 (1=the best and 10=the worst outcome). Statistical analysis was performed with IBM SPSS V23.Results:Most of the participants were worried about the needle, the dentist, and pain, respectively (38.2%, 34%, 28.2%). Most of the children raised their hand as a stop signal (94.7%). There was a statistically significant negative and weak correlation between age and anticipated pain, actual pain and anxiety scores (p=0.016, 0.003, 0.001 respectively).Conclusion:The "Message to the Dentist" feedback form and cognitive behavioral therapy resource can be used in pediatric dentistry to reduce dental anxiety in its Turkish version. It was useful to understand the sources of dental anxiety in children and this can facilitate treatment by helping pediatric dentists understand how these patients feel about dental treatment procedures and, via their efforts, to improve patient care.